HUBUNGAN DUKUNGAN ORANGTUA DAN TEMAN SEBAYA DENGAN KEDISIPLINAN BELAJAR SISWA - Lulu Retno Wulandari; Neviyarni Suhainil; Mudjiran - (Jurnal Penelitian Bimbingan dan Konseling, 2017)
Any student who has a learning discipline will be able to steer itself and control the behavior. Parent support not only provides the facility to go to school, but the closeness with the child can help him learn and solve problems together.This study used a quantitative method with correlative descriptive. The population were 370 students of SMK Agriculture 2 Tugumulyo. Sample of this research were 192 students that selected by Proportional Stratified Random Sampling. The discover research showed that: the positive significant correlation between parent support with learning discipline was about 32.5%,, the positive significant correlation between peer support with learning discipline was about 30.6%, and the positive significant correlation between parent support and peer with learning discipline was about 43.4%. The implication of these result could be used as an analysis need assesment in the preparation of guidance and counseling services program in schools. of SMK Agriculture 2 Tugumulyo Musi Rawas Sumatera Selatan Keywords : Parent Support, Peer Support, Learning Discipline.